ECONOMIC ASPECTS OF DRIED FRUIT PRODUCTION BY COMBINED TECHNOLOGY - Vukoje, Veljko; Pavkov, Ivan; Miljatović, Aleksandar (Economics of Agriculture, 2018)
The aim of the paper is to evaluate the level of profitability of dried fruit production by combined technology (osmotic and convective). In the focus of the research is small capacity dryer - 500 kg of fresh fruit per day, which is used on agricultural holding. The costs of fresh fruit are the most important item in the structure of the price of all types of fruit (67.1% on average), followed by labor costs (14.0%) and packaging (6.8%), while the share of energy is very modest (2.74%). Comparative analysis shows that, individually, the most cost-effective is dried pears production. For 120 days of effective operation of the dryer, profit of 9,815 € is realized, with an acceptable degree of coefficient of economic efficiency (1.21). Investment in construction of drier (31,900 €) is paid in 2.74 years. It is a profitable business, which can be a good source of income for agricultural holdings.